2006
DOI: 10.1051/apido:2006034
|View full text |Cite
|
Sign up to set email alerts
|

Water content of stingless bee honeys (Apidae, Meliponini): interspecific variation and comparison with honey ofApis mellifera

Abstract: -Honey samples were taken on both islands of the country of Trinidad and Tobago, from colonies of Melipona favosa, Melipona trinitatis, Plebeia tobagoensis, Trigona nigra and Apis mellifera. The Moisture Content (MC) of honeys of the various bee species differed significantly. The honey of the smaller species, P. tobagoensis and T. nigra, had higher MC values than that of the larger Melipona. The highest MC value was found in honey from P. tobagoensis (42.0%). The other MC values were 36.2% for T. nigra, 31.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 9 publications
1
17
0
4
Order By: Relevance
“…KH in this study were reported to have moisture content of 21.4-31.59%. Trigona nigra honey contained 36.2% of moisture (Bijlsma et al, 2006) and Trigona carbonaria honey possessed a moisture content of 26.2% (Oddo et al, 2008). The seasonal weather conditions and regional humidity of collection areas are the main factors that influence the moisture content which might be able to explain the great difference of moisture content among honey from different regions of this study.…”
Section: Total Soluble Solids Ph Moisture and Ash Content Of Khmentioning
confidence: 74%
“…KH in this study were reported to have moisture content of 21.4-31.59%. Trigona nigra honey contained 36.2% of moisture (Bijlsma et al, 2006) and Trigona carbonaria honey possessed a moisture content of 26.2% (Oddo et al, 2008). The seasonal weather conditions and regional humidity of collection areas are the main factors that influence the moisture content which might be able to explain the great difference of moisture content among honey from different regions of this study.…”
Section: Total Soluble Solids Ph Moisture and Ash Content Of Khmentioning
confidence: 74%
“…Lastly, a chemical transformation occurs when the worker bees secrete the enzymes from their cephalic glands that are able to hydrolyse the nectar's sucrose into fructose and glucose [12,14]. Although it is hard to refute that the characteristics of honey vary depending on the bee species, nectar sources, and climate, the noteworthy similarity in stingless bee honey is the water content that is commonly higher than in other types of honey [15,16]. As a result, the rich water condition invites the microorganism to inhabit and thrive inside the honey.…”
Section: Introductionmentioning
confidence: 99%
“…Zuletzt durchläuft der Nektar eine chemische Umwandlung, bei der die im Sekret der Kopfdrüsen von Arbeiterinnen enthaltenen Enzyme eine hydrolytische Spaltung der Saccharose in Fruktose und Glukose bewirken [12,14]. Zwar lässt sich nicht bestreiten, dass die Eigenschaften eines Honigs je nach Bienenart, Nektarquellen und Klima unterschiedlich ausfallen, doch besteht eine wichtige Gemeinsamkeit der Honige stachelloser Bienen im Wassergehalt, der allgemein höher ist als bei anderen Honigarten [15,16] [23,24]. Verschiedene Studien haben weitere faszinierende biologische Wirkungen von Honig wie beispielsweise eine antinozizeptive [25,26], immunmodulatorische [27,28] …”
Section: Cerumen Und Honigproduktion Im Gefäßunclassified